Numerical simulation of organic semiconductor devices with high carrier densities - Stodtmann, Sven; Lee, R. M.; Weiler, Christoph Karl Felix (Journal of applied physics, 2012)
We give a full description of the numerical solution of a general charge transport model for doped disordered semiconductors with arbitrary field- and density-dependent mobilities. We propose a suitable scaling scheme and generalize the Gummel iterative procedure, giving both the discretization and linearization of the van Roosbroeck equations for the case when the generalized Einstein relation holds. We show that conventional iterations are unstable for problems with high doping, whereas the generalized scheme converges. The method also offers a significant increase in efficiency when the injection is large and reproduces known results where conventional methods converge.
Gesehen am 09.10.2020